Religious Reality in MUI Fatwa Number 2 of 2022 on Uang Panai': A Philosophical Analysis of the Social Dynamics of the Makassar Bugis Community - Idrus, Achmad Musyahid; Qayum, Abdul Rahman; Abbas, Rahmawati; Maulidah, Tahani Asri (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2025)
Panai money in the marriage tradition of the Bugis Makassar community has caused many realities in people's lives, one of these realities is reality. This research intends to find answers to the two problems studied in this study, namely how the religious reality of panai money and how the typology of the law caused by panai money. The method used in this research is a descriptive kaulitative method by highlighting the philosophical analysis of the reality of the panai money. The result of the research is the religious reality of panai money that is widely developed in the life of the Bugis Makassar community is the rampant loan of panai money, and the legal typology arising from the loan of panai money is permissible on the one hand and can be haram on the other. The conclusion of this research is that people have different views on the legal status of panai money loans.